Heterogeneity in marginal returns to language training of immigrants - Matthias Giesecke; Eric Schuss (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
We estimate the effect of language training on subsequent employment and wages of immigrants under essential heterogeneity. The identifying variation is based on regional differences in language training availability that we use to instrument endogenous participation. Estimating marginal treatment effects along the distribution of observables and unobservables that drive individual participation decisions, we find that immigrants with higher gains are more likely to select into language training than immigrants with lower gains. We document up to 15 percent higher employment rates and 13 percent wage gains for immigrants with a high desire to participate but the positive returns vanish with increasing resistance to treatment. This pattern of selection on gains correlates with unobserved ability and motivation, promoting investments in education and job-specific skills that yield higher returns when complemented by language capital in the host country. – – Die Studie untersucht den Effekt von Sprachkursen auf Beschäftigung und Löhne von Immigranten. Die Identifikation basiert auf einer Instrument-Variable, die exogene Variation in der regionalen Verfügbarkeit von Sprachkursen nutzt. Anhand dieses Instruments werden marginale Treatment-Effekte (MTE) entlang der Verteilung beobachtbarer und unbeobachtbarer Variablen geschätzt. Die Ergebnisse zeigen, dass Immigranten mit höheren Erträgen aus der Teilnahme sich wahrscheinlicher in Sprachkurse selektieren als Immigranten mit geringeren Erträgen. Personen mit hoher Teilnahmepräferenz weisen eine um 15 Prozent höhere Beschäftigungsquote und bis zu 13 Prozent höhere Löhne auf. Die positiven Effekte werden mit abnehmender Teilnahmewahrscheinlichkeit schwächer und verschwinden schließlich vollständig. Diese Selektion nach Erträgen korreliert mit unbeobachtbaren Eigenschaften wie Motivation und Talent, die mit höheren Investitionen in Bildung und berufsspezifischen Qualifikationen einhergehen und zu höheren Erträgen führen, wenn sie durch Sprachkenntnisse des Gastlandes komplementiert werden.
Keywords: F22; J24; J61; J68; O15; 330; Continuous Instrument; Heterogeneous Returns; Language Training; Marginal Treatment Effects